Regionalism versus Multilateral Trade Arrangements. - Ito, Takatoshi (National Bureau of Economic Research-East Asia Seminar on Economics., 1997)
There is no doubt that the open multilateral trading system after World War II was a key ingredient in the rapid economic development of the entire world. Especially in Hong Kong, Korea, Singapore, and Taiwan, exports increased dramatically both in absolute terms and as a percentage of GNP. In the 1980s, however, preferential trading arrangements (PTAs) began to emerge as significant factors affecting world trade. This volume contains thirteen papers that analyze the tensions between multilateral trading systems and preferential trade arrangements and the impact of these tensions on East Asia.